2010
DOI: 10.3945/ajcn.2009.28424
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and health outcomes over 5 y in older women

Abstract: Vitamin D insufficiency is more common in older, frailer women. Community-dwelling older women with a seasonally adjusted 25(OH)D concentration <50 nmol/L were not at risk of adverse outcomes over 5 y after control for comorbidities. Randomized placebo-controlled trials are needed to determine whether vitamin D supplementation in individuals with vitamin D insufficiency influences health outcomes. This trial was registered at www.anzctr.org.au as ACTRN 012605000242628.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 42 publications
3
96
2
Order By: Relevance
“…Patients with impaired renal function are prone to secondary hyperparathyroidism and subsequently, a high risk of fracture (36). Conversely, some epidemiological studies claim that high Ca intake promotes calcification of the coronary arteries and subsequently increases the risk of myocardial infarction in older women (37)(38)(39). However, Samelson et al (40) recently published the results of their prospective observational cohort study in which they found no evidence that additional Ca intake in dietary food sources had any effect on coronary artery calcification.…”
Section: Discussionmentioning
confidence: 86%
“…Patients with impaired renal function are prone to secondary hyperparathyroidism and subsequently, a high risk of fracture (36). Conversely, some epidemiological studies claim that high Ca intake promotes calcification of the coronary arteries and subsequently increases the risk of myocardial infarction in older women (37)(38)(39). However, Samelson et al (40) recently published the results of their prospective observational cohort study in which they found no evidence that additional Ca intake in dietary food sources had any effect on coronary artery calcification.…”
Section: Discussionmentioning
confidence: 86%
“…However, protein supplementation studies have failed to consistently demonstrate benefit (75) although investigation of the role of protein supplementation as part of a multifactorial intervention is ongoing (76) . Additionally, although vitamin D receptors are found on skeletal muscle cells and myopathy is a feature of vitamin D deficient diseases, low serum vitamin D is not always associated with low physical function (77)(78)(79)(80)(81) in observational studies and supplementation studies also show mixed results (72,82,83) . However, the recognition of sarcopenia and frailty as important medical syndromes has fuelled interest in the development of effective interventions and it is likely that this will be an area of change over the coming few years.…”
Section: Relationship Between Sarcopenia and Frailtymentioning
confidence: 99%
“…In addition to these studies, a study from Israel, 10 including more than 180,000 participants, observed an 85% higher all-cause mortality in participants 11 in the bottom quartile (< 33.8 nmol/L) compared with the top quartile (> 65.2 nmol/L) [7]. The largest 12 study so far, which included almost 250,000 Danish men and women, reported an increased all-cause 13 mortality (RR=2.13, 95% CI 2.02-2. from the US [14][15][16][17], Finland [18], Sweden [12], and Germany [19] and a recent meta-analysis 6 reported a pooled relative risk of 1.42 (95% CI 1.19-1.71) for CVD mortality when comparing the 7 lowest with the highest 25(OH)D categories. [20].…”
Section: Introductionmentioning
confidence: 99%